2001
DOI: 10.4049/jimmunol.166.8.4818
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Characterization of Allorestricted and Peptide-Selective Alloreactive T Cells Using HLA-Tetramer Selection

Abstract: The vast majority of alloreactive T cells recognize foreign MHC molecules in a peptide-dependent manner. A subpopulation of these peptide-dependent alloreactive T cells is peptide-specific and contains T cells that are of interest for tumor immunotherapy. Allorestricted T cells (i.e., peptide-specific and alloreactive) specific for tumor-associated Ags can be raised in vitro. However, it is technically difficult to distinguish between peptide-specific and peptide-nonspecific alloreactive T cells by functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 38 publications
0
38
0
Order By: Relevance
“…Because the tetramer-negative cells are not peptide independent, we assume that they comprise T cells specific for other peptides from among the many known to be bound endogenously by HLA-A*0201 (27). Two reports describe examples of alloreactive T cells that are peptidedependent but not peptide-specific based on their ability to bind tetramers comprising several different peptide combinations presented by HLA-A*0201 (6,34). However, in both studies, the T cells were produced by stimulation with high densities of a single HLA class I/peptide combination that may artificially promote MHC structure-specific recognition.…”
Section: Discussionmentioning
confidence: 99%
“…Because the tetramer-negative cells are not peptide independent, we assume that they comprise T cells specific for other peptides from among the many known to be bound endogenously by HLA-A*0201 (27). Two reports describe examples of alloreactive T cells that are peptidedependent but not peptide-specific based on their ability to bind tetramers comprising several different peptide combinations presented by HLA-A*0201 (6,34). However, in both studies, the T cells were produced by stimulation with high densities of a single HLA class I/peptide combination that may artificially promote MHC structure-specific recognition.…”
Section: Discussionmentioning
confidence: 99%
“…Several TCR͞peptide͞MHC crystal structures have shown that the ␣1-and ␣2-helices of the MHC molecules are contacted by the TCR ␣-and ␤-chain complementarity-determining regions (CDR)1͞CDR2, the bound peptides interacting essentially with the hypervariable CDR3s (4). The dual selectivity of some alloreactive CTL clones for a given allogeneic molecule and a given peptide presented by this molecule might suggest that effective TCR͞MHC molecule interaction always requires a direct participation of the bound ligand (5,6). However, less stringent peptide selectivity has been documented for other CTL clones (7,8), suggesting in those cases predominant TCR interaction with the ␣1␣2-helices of their allogeneic MHC molecular targets.…”
Section: Ost Histocompatibility Class I Molecules Have An Openmentioning
confidence: 99%
“…[11][12][13][14] Further, characterization, cloning and expression of tumor-specific T cell receptors (TCRs) derived from such T cells and their subsequent expression in T cells for adoptive transfer 15 is now an established procedure. Landmark clinical trials with a TCR specific for NY-ESO-1 already demonstrated the great potential of this approach.…”
Section: Introductionmentioning
confidence: 99%